2000
DOI: 10.1002/(sici)1097-4695(200003)42:4<437::aid-neu5>3.3.co;2-f
|View full text |Cite
|
Sign up to set email alerts
|

Spinal motor axons and neural crest cells use different molecular guides for segmental migration through the rostral half-somite

Abstract: The peripheral nervous system in vertebrates is composed of repeating metameric units of spinal nerves. During development, factors differentially expressed in a rostrocaudal pattern in the somites confine the movement of spinal motor axons and neural crest cells to the rostral half of the somitic sclerotome. The expression patterns of transmembrane ephrin-B ligands and interacting EphB receptors suggest that these proteins are likely candidates for coordinating the segmentation of spinal motor axons and neura… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2000
2000
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 20 publications
(30 reference statements)
1
15
0
Order By: Relevance
“…Dose‐dependent analyses showed that optimal T140 inhibition of DPSC‐mediated TG axon guidance occurred at 5 μM (data not shown). The human‐chick chimeric embryos 2 hpi were explanted onto Millipore membranes and grown ex ovo in serum‐free defined media [30] supplemented with T140 or control peptide (Figs. 1E, 1F, Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Dose‐dependent analyses showed that optimal T140 inhibition of DPSC‐mediated TG axon guidance occurred at 5 μM (data not shown). The human‐chick chimeric embryos 2 hpi were explanted onto Millipore membranes and grown ex ovo in serum‐free defined media [30] supplemented with T140 or control peptide (Figs. 1E, 1F, Fig.…”
Section: Resultsmentioning
confidence: 99%
“…GFP‐transduced adult human DPSCs (5 × 10 3 cells/μl) were maintained in growth media alone or in the presence of CXCL12/SDF‐1, inhibitor T140 [27–29], or control peptide (RTVAHHGGLYHTNAEVK) (5 μM) (Mimotope, Victoria, Australia) before transplantation into the avian embryo. DPSCs were injected as described above, embryos were then dissected from the egg 2 hours postinjection, washed in Ringer's solution, and explanted onto a Millipore membrane (Millipore, Billerica, MA, http://www.millipore.com), as described previously [30]. The embryos were orientated so that the vitelline membrane (ventral side down) was in contact with the Millipore membrane bathed in Neurobasal Medium (GIBCO BRL, Grand Island, NY, http://www.invitrogen.com), B27 supplement (GIBCO BRL), and 0.5 mM L ‐glutamine (GIBCO BRL) with T140 or control peptide.…”
Section: Methodsmentioning
confidence: 99%
“…3). The cells of the DRG arise from the neural crest cells that migrate from the neural tube and undergo a distinct developmental programme (Koblar et al 2000). In neural migration, the centrosome is initially located ahead of the nucleus in the direction of migration (Gregory et al 1988).…”
Section: Discussionmentioning
confidence: 99%
“…Eph‐family receptors and their ligands are also involved in interactions between neural crest and sclerotomal cells (Krull et al. 1997; Wang & Anderson 1997; Koblar et al. 2000; McLennan & Krull 2002; Santiago & Erickson 2002; Kasemeier‐Kulesa et al.…”
Section: Introductionmentioning
confidence: 99%